Diseño optimizado de un brazo robótico antropomórfico validado por señales biomecánicas (2024)
This work seeks to design a 3D model of an anthropomorphic robotic arm. For this, reference biomechanical signals were used with which the torque profiles produced by the most critical joints were compared and their behavior was reviewed. By implementing the CAD models in Matlab/Simulink and replicating the movements of the reference arm, it was found that, although the mean square error is in most cases high, the torque profiles produced by the anthropomorphic arms follow the shapes of the reference torques. Likewise, designs were obtained that are capable of having a minimum difference in torques at the critical points, or maximums, thereby obtaining a design capable of representing an initial design parameter for different arms.